Hypotrichotic nevus (congenital triangular alopecia). - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
A 9-year-old boy was first observed due to alopecia areata at the nape. However, his mother said that the alopecic area had been present from the first period of life and had not changed substantially over time, despite the many topical therapies made. The family history was negative for alopecia areata and other autoimmune diseases. His family and personal history was negative for atopy. The physical examination highlighted at the back hair line a round area of about 2 cm, apparently devoid of hair (Fig. 1). At closer observation thin and less pigmented hair (Fig. 2) could be observed. The dermoscopic observation (Fig. 3) confirmed the clinical finding showing also the absence of pseudocomedos, of "cadaverized" and exclamation mark hairs and thus leading to the final diagnosis of hypotrichotic nevus.